ORGANIZATIONAL, MORPHOLOGICAL, STRUCTURAL FEATURES OF BRONZE POWDER MANUFACTURE FROM CHIP WASTE - Морозов, Андрей; Омельченко, Ирина (SWorldJournal, 2021)
The object of research was practical technology receiving of metal powders from clip waste of aluminum bronze with their subsequent use as pigments for printing processes. In the course of research was found that the developed surface of chip particles, n